Performance Prediction Through OEE-Model - Anusha, Chintada; Umasankar, Venkata (International Journal of Industrial Engineering and Management, 2020)
Prediction of an organization’s performance has become essential for any organization for its potential customers to place orders with confidence. Overall Equipment Effectiveness (OEE) is one of the acknowledged measures for performance monitoring. In this paper, two different techniques, a simple moving average and Holt’s double exponential smoothing methods, are used to evaluate OEE and to predict the future performance of overall equipment effectiveness in R studio. Holts Double exponential smoothing method was found to result in minimum error measured by mean absolute deviation. Python program is to predict major losses to improve the productivity of the organization by management. Article history: Received (October 03, 2020); Revised (April 02, 2020); Accepted (April 02, 2020); Published online (April 29, 2020)